Photochemical outcomes triggered by gold shell-isolated nanorods on bioinspired nanoarchitectonics for bacterial membranes - Almeida Junior, Alexandre Mendes; Moreira, Lucas Gontijo; Camacho, Sabrina Alessio; Ferreira, Fabiana G.; Conceição, Katia; Tada, Dayane Batista; Aoki, Pedro Henrique Benites (Elsevier, 2023)
Boosted by the indiscriminate use of antibiotics, multidrug-resistance (MDR) demands new strategies to combat bacterial infections, such as photothermal therapy (PTT) based on plasmonic nanostructures. PTT efficiency relies on photoinduced damage caused to the bacterial machinery, for which nanostructure incorporation into the cell envelope is key. Herein, we shall unveil the binding and photochemical mechanisms of gold shell-isolated nanorods (AuSHINRs) on bioinspired bacterial membranes assembled as Langmuir and Langmuir-Schaefer (LS) monolayers of DOPE, Lysyl-PG, DOPG and CL. AuSHINRs incorporation expanded the isotherms, with stronger effect on the anionic DOPG and CL. Indeed, FTIR of LS films revealed more modifications for DOPG and CL owing to stronger attractive electrostatic interactions between anionic phosphates and the positively charged AuSH INRs, while electrostatic repulsions with the cationic ethanolamine (DOPE) and lysyl (Lysyl-PG) polar groups might have weakened their interactions with AuSHINRs. No statistical difference was observed in the surface area of irradiated DOPE and Lysyl-PG monolayers on AuSHINRs, which is evidence of the restricted nano structures insertion. In contrast, irradiated DOPG monolayer on AuSHINRs decreased 4.0 % in surface area, while irradiated CL monolayer increased 3.7 %. Such results agree with oxidative reactions prompted by ROS gener ated by AuSHINRs photoactivation. The deepest AuSHINRs insertion into DOPG may have favored chain cleavage while hydroperoxidation is the mostly like outcome in CL, where AuSHINRs are surrounding the polar groups. Furthermore, preliminary experiments on Escherichia coli culture demonstrated that the electrostatic interactions with AuSHINRs do not inhibit bacterial growth, but the photoinduced effects are highly toxic, resulting in microbial inactivation.

Impulsionada pelo uso indiscriminado de antibióticos, a resistência a múltiplos medicamentos (MDR) exige novas estratégias para combater infecções bacterianas, como a terapia fototérmica (PTT) baseada em nanoestruturas plasmônicas. A eficiência da PTT depende dos danos fotoinduzidos causados à maquinaria bacteriana, sendo a incorporação de nanoestruturas no envelope celular um fator chave. Aqui, desvendaremos os mecanismos de ligação e fotoquímicos de nanobastões de ouro recobertos (AuSHINRs) em membranas bacterianas bioinspiradas montadas como monocamadas de Langmuir e Langmuir-Schaefer (LS) de DOPE, Lysyl-PG, DOPG e CL. A incorporação de AuSHINRs expandiu as isotermas, com efeito mais pronunciado nos lipídios aniônicos DOPG e CL. De fato, o FTIR de filmes LS revelou mais modificações para DOPG e CL, atribuídas a interações eletrostáticas atrativas mais fortes entre os fosfatos aniônicos e as AuSHINRs carregados positivamente, enquanto repulsões eletrostáticas com os grupos polares catiônicos etanolamina (DOPE) e lisil (Lysyl-PG) podem ter enfraquecido suas interações com as AuSHINRs. Não foi observada diferença estatística na área de superfície das monocamadas de DOPE e Lysyl-PG irradiadas com AuSHINRs, evidenciando uma inserção restrita das nanoestruturas. Em contraste, a monocamada de DOPG irradiada com AuSHINRs apresentou uma redução de 4,0% na área de superfície, enquanto a monocamada de CL irradiada aumentou 3,7%. Esses resultados estão de acordo com reações oxidativas desencadeadas por espécies reativas de oxigênio (ROS) geradas pela fotoativação dos AuSHINRs. A inserção mais profunda das AuSHINRs no DOPG pode ter favorecido a clivagem de cadeias, enquanto a hidroperoxidação parece ser o principal efeito no CL, onde as AuSHINRs cercam os grupos polares. Além disso, experimentos preliminares com culturas de Escherichia coli demonstraram que as interações eletrostáticas com as AuSHINRs não inibem o crescimento bacteriano, mas os efeitos fotoinduzidos são altamente tóxicos, resultando na inativação microbiana.
Resultados fotoquímicos desencadeados por nanobastões de ouro recobertos em nanoarquiteturas bioinspiradas de membranas bacterianas
Keywords: Gold shell-isolated nanorods (AuSHINRs); Photothermal therapy; Bioinspired bacterial membranes